2016
DOI: 10.1016/j.jep.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Derris scandens (Roxb.) Benth. for musculoskeletal pain treatment: A systematic review and meta-analysis of randomized controlled trials

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. scandens showed no different relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In Thailand, it has been used traditionally for pain treatment. [ 1 ] Phytochemical studies of the plant have shown that its stems contain various bioactive compounds, such as flavonoids and terpenoids. [ 2 ] Among these compounds, the isoflavone genistein was determined to exhibit anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, it has been used traditionally for pain treatment. [ 1 ] Phytochemical studies of the plant have shown that its stems contain various bioactive compounds, such as flavonoids and terpenoids. [ 2 ] Among these compounds, the isoflavone genistein was determined to exhibit anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…4 The crude drug of D. scandens stem was also reported that it significantly reduced muscle pain in patients with osteoarthritis and low back pain, with the similar adverse reactions to that of NSAIDs. 3,20,21 Moreover, chloroform extract of leaf and root and aqueous extract of stem of D. scandens exhibited anti-inflammatory activity in the carrageenan-induced paw oedema in rat model and they inhibited eicosanoid inflammatory mediator. 22,23 For Clinical studied found that there were no differences in efficacy and safety in the treatments of knee osteoarthritis with D. scandens crude for seven consecutive days and ibuprofen.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 21 ] demonstrated that acupuncture analgesia is effective in reducing pain. In Thailand, Derris scandens has been widely used to reduce musculoskeletal pain [ 22 ].…”
Section: Discussionmentioning
confidence: 99%